A taxonomic and taphonomic study of Pleistocene fossil deposits from the western Nefud Desert, Saudi Arabia. Issue 1 (May 2020) - Stewart, Mathew; Louys, Julien; Breeze, Paul S.; Clark-Wilson, Richard; Drake, Nick A.; Scerri, Eleanor M.L.; Zalmout, Iyad S.; Al-Mufarreh, Yahya S. A.; Soubhi, Saleh A.; Haptari, Mohammad A.; Alsharekh, Abdullah M.; Groucutt, Huw S.; et al.
Abstract: Over the past decade, a growing interest has developed on the archaeology, palaeontology, and palaeoenvironments of the Arabian Peninsula. It is now clear that hominins repeatedly dispersed into Arabia, notably during pluvial interglacial periods when much of the peninsula was characterised by a semiarid grassland environment. During the intervening glacial phases, however, grasslands were replaced with arid and hyperarid deserts. These millennial-scale climatic fluctuations have subjected bones and fossils to a dramatic suite of environmental conditions, affecting their fossilisation and preservation. Yet, as relatively few palaeontological assemblages have been reported from the Pleistocene of Arabia, our understanding of the preservational pathways that skeletal elements can take in these types of environments is lacking. Here, we report the first widespread taxonomic and taphonomic assessment of Arabian fossil deposits. Novel fossil fauna are described and overall the fauna are consistent with a well-watered semiarid grassland environment. Likewise, the taphonomic results suggest that bones were deposited under more humid conditions than present in the region today. However, fossils often exhibit significant attrition, obscuring and fragmenting most finds. These are likely tied to wind abrasion, insolation, and salt weathering following fossilisation and exhumation, processes particularly prevalent in desert environments.